Longitudinal trajectories of behavior change in a national sample of patients seeking eating‐disorder treatment. Issue 6 (10th April 2020) - Chapa, Danielle A. N.; Hagan, Kelsey E.; Forbush, Kelsie T.; Clark, Kelsey E.; Tregarten, Jenna P.; Argue, Stuart
Abstract: Objective: Rapid response to treatment, indicated by substantial decreases in eating‐disorder (ED) symptoms within the first 4–6 weeks of treatment, is the most reliable predictor of treatment outcomes for EDs. However, there is limited research evaluating short‐term longitudinal trajectories of ED symptoms during treatment. Thus, it is difficult to know which aspects of ED psychopathology are slow or fast to change. The purpose of this study was to elucidate three‐month trajectories of ED psychopathology during treatment and test whether ED diagnosis influenced the direction and rate of change. Method: Participants were Recovery Record users seeking treatment for an ED ( N = 4, 568; 86.8% female). Participants completed the Eating Pathology Symptoms Inventory once per month for 3 months. Results: Latent growth curve models indicated that ED diagnosis influenced the rate of ED behavior change. Anorexia nervosa was associated with faster reductions in cognitive restraint, excessive exercise, restricting, yet slower reductions in body dissatisfaction, and binge eating. Bulimia nervosa was associated with faster reductions in binge eating, cognitive restraint, excessive exercise, and purging. Binge‐eating disorder was associated with faster reductions in body dissatisfaction and binge eating, yet slower reductions in restricting. Conclusions: Our results have implications for future research by providing initial information about the direction and rate of ED change over the course of treatment. If clinicians and researchers know which ED symptoms are slow to change, on average, across diagnostic groups, treatment protocols could be adjusted to target slow changing symptoms more quickly, and therefore improve ED treatment outcomes.